Strength resistance factors for seismic design of exposed based plate connections in special steel moment resisting frames. Issue 2 (May 2020) - Torres-Rodas, Pablo; Fayaz, Jawad; Zareian, Farzin
This study presents a critical assessment of the reliability of current base plate connections in steel special moment resisting frames (SMRFs). Using a probabilistic outlook, this research evaluates the reliability of exposed column base (ECB) connections in SMRFs designed based on the current seismic design provisions; it suggests (and implements) a statistical approach to compute resistance factors for three modes of failure (concrete bearing, base plate yielding at tensile interface, and anchor bolt fracture) of ECB connections to achieve a target reliability index, β, of 4.5. Since ECB connections are limited to short buildings, therefore, this study is conducted on two-story and four-story SMRFs which are analyzed using a suite of 120 ground motions originating from strike-slip and reverse faults. ECB connections for the two-story building are designed to simulate pinned connection, while the bases of the four-story building represent moment connections. Detailed methodology for calculating the β of ECB connections is presented considering the three limit states in a moment–axial load interaction curve. Results indicate that the implementation of current seismic provisions results in β ~ 3.3 for non-moment resisting ECB connections for all tried combinations of resistance factors. For moment resisting ECB connections, however, only the designs based on a resistance factor for concrete bearing failure mode less than the current 0.65 result in an acceptable reliability factor of β  > 4.5.